A Data Solution Approach Based on Data Mining for Vegetable Cultivation in terms of Ecological - Ucar, Ukbe; Balo, Figen (Ieee, 2018)
In today's world, technological developments and increasing population increase cause rapid depletion of natural resources. Vegetable and similar plants, which have a great importance in terms of the continuity of life and ecological sustainability, are at the top of rapidly consumed resources and the lack of these plants causes serious problems in nature. Vegetable growing is of great importance in meeting the increased demand for vegetables and in ensuring ecological balance. Vegetable farming is one of the main export items of many countries, and many farmers are making significant investments this field. To make successful investments, to obtain efficient and quality products, proper investment policies need to be made. In this study, a decision support system based on data mining has been developed to ensure efficient use of land, to contribute to ecological balance, and to correctly direct investment in vegetable growing. Thanks to this system, it is aimed to determine suitable vegetable species which can be grown in the related region under the geographical and climatic constraints.
Ekolojik Açidan Sebze Yetiştiricili?i Için Veri Madencili?ine Dayali Bir çözüm Yaklaşimi
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Decision Tree; Vegetable Farming; Classification of Vegetable; Decision Support System